PENGARUH MOTIVASI BELAJAR DAN MINAT BELAJAR TERHADAP HASIL BELAJAR IPA PESERTA DIDIK PADA ERA MERDEKA BELAJAR - Agung Riadin; endang sri estimurti (Jurnal Holistika, 2022)
Interest and motivation is one of the supporting components so that students are able to produce quality learning outcomes. Motivation and interest ultimately have a significant impact on learning outcomes. This study aims to determine the effect of learning motivation and interest in learning on the learning outcomes of students, especially in the era of independent learning. The research method used is quantitative. The population and sample in this study were students from three schools totaling 105 people. The research instrument used was a questionnaire about learning motivation, interest in learning and student learning outcomes tests. Analysis of the data used in this study is quantitative analysis with the help of SPSS. The results showed that there was an influence between interest and motivation on learning outcomes. For teachers should be able to generate interest and motivation of students. A teacher in delivering lessons must be able to make students happy in learning. With the interest and motivation that arises, great effort is made to learn the lesson, and it is hoped that students will get good learning outcomes. Teachers need to pay close attention to students so that they have good interest and motivation in learning so that in the end the desired learning outcomes are achieved